2015
DOI: 10.26719/2015.21.9.665
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hand hygiene compliance in Egypt: building blocks for a communication strategy

Abstract: Hand hygiene of health-care staff is one of the most important interventions in reducing transmission of nosocomial infections. This qualitative study aimed to understand the behavioural determinants of hand hygiene in order to develop sustainable interventions to promote hand hygiene in hospitals. Fourteen focus group discussions were conducted with nurses in 2 university hospitals in Egypt. The interviews were tape recorded and transcribed. Thematic analysis was conducted by 2 independent investigators. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Dixon-Woods [32] identified 10 challenges to the successful implementation of QI projects, including convincing workers there is a problem, overcoming the burden of data collection, improving the organizational leadership and lack of staff engagement. Studies have also shown that two limitations to complying with hand hygiene protocol include lack of resources to properly dry hands with clean towels [33] and a failure to associate poor hand hygiene with unseen bacteria instead of a feeling of ‘dirtiness’ [34]. Use of implementation frameworks such as the ISF allow for the identification of local determinants affecting implementation and for the creation of locally acceptable implementation strategies.…”
Section: Initial Assessment and Choice Of Solutionmentioning
confidence: 99%
“…Dixon-Woods [32] identified 10 challenges to the successful implementation of QI projects, including convincing workers there is a problem, overcoming the burden of data collection, improving the organizational leadership and lack of staff engagement. Studies have also shown that two limitations to complying with hand hygiene protocol include lack of resources to properly dry hands with clean towels [33] and a failure to associate poor hand hygiene with unseen bacteria instead of a feeling of ‘dirtiness’ [34]. Use of implementation frameworks such as the ISF allow for the identification of local determinants affecting implementation and for the creation of locally acceptable implementation strategies.…”
Section: Initial Assessment and Choice Of Solutionmentioning
confidence: 99%
“…Borg et al (2009) found self-reported compliance to hand hygiene to be higher following direct patient contact, or when hands were visibly dirty. The sense that a patient was unclean due to having open wounds or body odour has also been found to be a prompt for hand cleansing, with this feeling extending to patient unfriendliness or erratic behaviour (Lohiniva et al, 2015). The inherent need to clean one's hands drives the majority of hand hygiene behaviour and stems from the emotion of disgust and feelings of self-protection (Curtis and Biran, 2001;World Health Organization, 2009).…”
Section: Psychological Factors In Hand Hygiene Behaviourmentioning
confidence: 99%